Pengaruh Limbah Mikroplastik Terhadap Organisme dan Upaya Penanganannya - Alfarros Amar Amanu; Alya Puspita Zahrani; Fitrin Aeni Ristaatin; Alfin Riski Ardillah; Denny Oktavina Radianto (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
In the midst of rapid industrial progress and global economic growth, the use of plastic has increased dramatically, causing serious environmental problems due to the accumulation of plastic waste. One of the most worrying aspects of this problem is the presence of microplastics, namely plastic particles less than five millimeters in size. The more accumulation of plastic waste found in the waters will cause damage to the surrounding water and sea environment, plastic waste that is not collected will be exposed to sunlight and exposure to air, the longer it will decompose into small particles called microplastics. In this research, the author researched using the library research method, namely by collecting and studying existing literature from various sources such as: journals, articles, books and others related to this research. Microplastics have spread widely in the environment, from oceans to land, and have had a serious impact on organisms and ecosystems throughout the world. The process by which microplastics are formed, their distribution in the environment, their impact on aquatic and terrestrial organisms, and their potential impact on human health are the main focus research and public attention. To overcome the microplastic problem, a holistic approach is needed that involves collaboration across sectors and scientific disciplines. Handling and mitigation efforts must cover various aspects, starting from regulating the use of single-use plastics, more effective management of plastic waste, developing technology for detecting and eliminating microplastics, to educating the public about the dangers of microplastics and the importance of environmentally friendly behavior. Concrete steps such as banning the use of single-use plastics, promoting recycling, innovation in product design, and cross-border cooperation in managing plastic waste are key in efforts to reduce the negative impact of microplastics. Only by taking these steps together can we create a cleaner, healthier and more sustainable environment for future generations.